PROBIOTIC SUPPLEMENTATION OF YEAST TAPE (Saccharomyces spp.) IN RATION AGAINST THE PECENTAGE OF LOIN AND PHYSICAL COMPOSITION OF LANDRACE PIG LOIN CARCASS PRIMAL CUT - I P. R. Y., Pradana; Puspani, E.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the probiotic supplementation of yeast tape (Saccharomyces spp.) in ration against the percentage of loin and physical composition of cross breed Landrace pig loin carcass prime cut. The method applied in this study was a completely randomized design (CRD), contained with 4 treatments there are P0: cross breed Landrace pig ration given without probiotic yeast tape (Saccharomyces spp.) as the control, P1; cross breed Landrace pig is given ration under probiotic yeast tape (Saccharomyces spp.) of 0,1%, P2; cross breed Landrace pig is given ration under probiotic yeast tape (Saccharomyces spp.) of 0,2%, and P3; cross breed Landrace pig is given ration under probiotic yeast tape (Saccharomyces spp.) of 0,3%. The treatments were conducted in 4 times replication. The variable that observed involves percentage of loin and the presentation of carcass loin primal cut. The data were analyzed using variance observed. The results showed that probiotic Saccharomyces spp. (yeast tape) of 0,1% (P1), 0,2% (P2), and 0,3% (P3) given can increase loin weight and carcass loin primal cut of cross breed Landrace pig compared with the pig given ration without yeast tape (Saccharomyces spp.) addition and statistically significantly different (P<0,05). It can be concluded that probiotic given yeast tape (Saccharomyces spp.) in the cross breed Landrace pig can increase loin weight and carcass loin primal cut. Probiotic yeast tape (Saccharomyces spp.) of 0,3% given is the optimal treatment. Keywords: yeast tape (Saccharomyces spp.), probiotic, loin, cross breed Landrace pig